Low torcular Herophili position and large brainstem–tentorium angle in fetuses with open spinal dysraphism at 11–13 weeks' gestation. (5th January 2022) - Volpe, P.; De Robertis, R.; Fanelli, T.; Boito, S.; Volpe, G.; Votino, C.; Persico, N.; Chaoui, R.
ABSTRACT: Objective: To evaluate whether in fetuses with open spina bifida (OSB) the tentorium can be seen to be displaced downwards and vertically oriented by the time of the 11–13‐week scan and whether this is reflected in an alteration of the brainstem–tentorium (BST) angle. Methods: The study population was recruited between 2015 and 2020 from three fetal medicine referral centers and comprised a control group and a study group of pregnancies with OSB. The control group was recruited prospectively and included singleton pregnancies with a normal sonographic examination after first‐trimester combined screening for chromosomal abnormalities and normal outcome. The study group was selected retrospectively and included all cases with OSB between 2015 and 2020. All cases underwent detailed ultrasound assessment at 11 + 0 to 13 + 6 weeks' gestation. The position of the torcular Herophili (TH) was identified in the midsagittal view of the fetal brain with the use of color Doppler and was considered as a proxy for the insertion of the tentorium on the fetal skull. The BST angle was calculated in the same view and was compared between the two groups. Results: Sixty normal fetuses were included in the control group and 22 fetuses with OSB in the study group. In both groups, the BST angle was found to be independent of gestational age or crown–rump length ( P = 0.8815, R 2 = 0.0003861 in the controls, and P = 0.2665, R 2 = 0.00978 in the OSB group). The mean BST angle was 48.7 ± 7.8° in controls and 88.1 ± 1.18°, i.e. close to 90°, in fetuses with OSB. Comparison of BST‐angle measurements between the control group and cases with OSB showed a statistically significant difference ( P = 0.0153). In all fetuses with OSB, the downward displacement of the TH and tentorium was clearly visible at the 11–13‐week scan. Conclusions: In fetuses with OSB, the BST angle is significantly larger than in normal controls, with the tentorium being almost perpendicular to the brainstem. This sign confirms the inferior displacement of the tentorium cerebelli with respect to its normal insertion on the occipital clivus as early as the first trimester of pregnancy and is useful in the diagnosis of Chiari‐II malformation at this early stage. In fetuses with OSB, the low position of the tentorium and TH is clearly visible, even subjectively, at the 11–13‐week scan. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.